Profiling of the muscle-specific dystroglycan interactome reveals the role of Hippo signaling in muscular dystrophy and age-dependent muscle atrophy - Yatsenko, Andriy S. (BMC Med, 2020)
BACKGROUND: Dystroglycanopathies are a group of inherited disorders characterized by vast clinical and genetic heterogeneity and caused by abnormal functioning of the ECM receptor dystroglycan (Dg). Remarkably, among many cases of diagnosed dystroglycanopathies, only a small fraction can be linked directly to mutations in Dg or its regulatory enzymes, implying the involvement of other, not-yet-characterized, Dg-regulating factors. To advance disease diagnostics and develop new treatment strategies, new approaches to find dystroglycanopathy-related factors should be considered. The Dg complex is highly evolutionarily conserved; therefore, model genetic organisms provide excellent systems to address this challenge. In particular, Drosophila is amenable to experiments not feasible in any other system, allowing original insights about the functional interactors of the Dg complex. METHODS: To identify new players contributing to dystroglycanopathies, we used Drosophila as a genetic muscular dystrophy model. Using mass spectrometry, we searched for muscle-specific Dg interactors. Next, in silico analyses allowed us to determine their association with diseases and pathological conditions in humans. Using immunohistochemical, biochemical, and genetic interaction approaches followed by the detailed analysis of the muscle tissue architecture, we verified Dg interaction with some of the discovered factors. Analyses of mouse muscles and myocytes were used to test if interactions are conserved in vertebrates. RESULTS: The muscle-specific Dg complexome revealed novel components that influence the efficiency of Dg function in the muscles. We identified the closest human homologs for Dg-interacting partners, determined their significant enrichment in disease-associations, and verified some of the newly identified Dg interactions. We found that Dg associates with two components of the mechanosignaling Hippo pathway: the WW domain-containing proteins Kibra and Yorkie. Importantly, this conserved interaction manages adult muscle size and integrity. CONCLUSIONS: The results presented in this study provide a new list of muscle-specific Dg interactors, further analysis of which could aid not only in the diagnosis of muscular dystrophies, but also in the development of new therapeutics. To regulate muscle fitness during aging and disease, Dg associates with Kibra and Yorkie and acts as a transmembrane Hippo signaling receptor that transmits extracellular information to intracellular signaling cascades, regulating muscle gene expression.